Evaluating perceived advantages and funding needs to enhance emergency medical services: insights from patients and staff - Valentin Dimitrov; Diana Pantileeva Dimitrova; Alexandrina Vodenicharova; Samir Dzhafer; Jannis Papathanasiou; Nigyar Dzhafer (Folia Medica, 2025)
Introduction: The University Hospital for Active Treatment and Emergency Medicine (UHATEM) “N. I. Pirogov” LTD is a pivotal institution in Bulgaria’s emergency medical services (EMS). However, funding challenges adversely affect its operational efficiency and quality of care. Aim: This study aims to identify the primary perceived advantages of UHATEM “N. I. Pirogov” LTD compared to other medical facilities, assess differences in perceptions between patients and staff, and evaluate the impact of funding limitations on hospital operations. Materials and methods: A cross-sectional study was conducted between January and July 2023 using a self-administered online questionnaire with 16 questions across four domains. A total of 1,041 participants were surveyed. Data analysis included descriptive statistics, chi-square tests, Cramér’s V, and one-way ANOVA to identify significant differences in perceptions and mean scores across age groups. Results: “Fast and fail-safe 24-hour access” was the most valued advantage among both patients and staff. The staff highlighted the hospital’s “multidisciplinary profile and teams” and “unique and unparalleled clinics and structures” as significant strengths. Chi-square analysis confirmed significant associations between perceived advantages and respondent type. Funding-related challenges, such as limited financial resources and high operational costs, were identified as critical issues. Conclusions: To improve EMS quality and sustainability at UHATEM “N. I. Pirogov” LTD, consistent state funding, public-private partnerships, and operational efficiencies are needed. Addressing these challenges is essential for maintaining high-quality care and operational stability.